Evaluation of Erosion Wear of Slurry Pump Materials - Singh, Jaspreet (My University, 2014)
Slurry erosion is the main problem in the transportation of fly ash. Pipelines and slurry pumps are used to transport fly ash over short to medium distance through. The slurry pumps are also used for other types of slurry transportation. Due to slurry erosion slurry pump parts losses the materials. Slurry not only erodes the material but also reduces the efficiency of the slurry pump. It is necessary to reduce the effect of slurry on pump to improve the efficiency and life. So the it become necessary to reduce the slurry effect with the use of slurry resist materials for pump. Mainly coatings are used to increase the slurry resistance. The main aim of this study is to increase the slurry resistance of the pump material. For this in this study Stainless Steel-202 grade and Grey Cast Iron is used under the effect of slurry erosion. A slurry of water and fly ash was prepared for this test. The fly ash for this purpose was collected from Guru Gobind Singh thermal plant, ropar (Punjab). To evaluate the slurry erosion Slurry Pot Tester is used. The used parameters of concentration 25 % and 45 %, speeds 800 rpm, 1100 rpm and 1400 rpm of the rotating spindle and time at 70, 120,170 and 220 minutes. To improve the performance of Grey cast iron and SS-202 coating is used. The used coating materials are Ni+Al2O3 and Ni+Cr2O3 by the thermal spraying method of HVOF. The experiment was performed on coated and uncoated of Grey Cast iron and SS-202 under the effect of different parameters. The XRD and SEM analysis was also done on the eroded and uneroded samples. Microhardness of the coated and uncoated samples was measured. After the experiment it was examined that the coated samples resisted erosion greater than the uncoated samples. It is concluded that performance of Ni+Cr2O3 coatings is better than Ni+Al2O3 coated
ME, MED
Keywords: Erosion Wear; slurry pump